A re-evaluation of the determinants of FDI in Malaysia - Abu Bakar, Nor'Aznin; Lau, Ming Sern (Universiti Utara Malaysia, 2005)
This paper examines the key determinants fo foreign direct investment (FDI) in Malaysia using time series analysis techniques that address the problem of non stationarity. Specifically, variables such as trade openness, infrastructure quality, market-size, human capital and natural resource are tested using the ADF and cointegration tests to ensure that the regression is not spurious. In line with several other empirical studies, result obtained comfirm that traditional factors such as market size are still dominant factors shaping the distribution of FDI in Malaysia, while the natural resource availability is the only insignificant variable. However, other non-traditional factors such as trade openness, agglomeration and human capital are also greatly increasing in importance, especially during this era of globalisation, Beside that, the complex global integration strategies adopted by multi-national companies (MNCs) which favour the presence of sophisticated and created assets in host countries over most other determinants also play an important role. Therefore, it is crucial that developing countries over most other determinants also play an important role. Therefore, it is crucial that developing countries formulate policies that improve local infrastructure, local skills and build up their human resourse capabilities to increase competition for FDI.